AN ANALYSIS OF AUTHENTIC MATERIALS USED BY ENGLISH TEACHER IN SENIOR HIGH SCHOOL IN SINGARAJA - K. Artha; A.A.I.N. Marhaeni; N.L.P.E.S. Dewi (Language and Education Journal Undiksha, 2020)
Many researchers suggested that the language taught in the classroom must reflect how it is usedby native speakers because there has been a gap between the language used in the classroom andthe language in real life. This study aimed to determine the level of authenticity of the material used bythe English teachers and also to find out the criteria that teachers use in choosing authentic material.This study used explanatory mix-method research where quantitative data results will be supported byqualitative data results. The subjects of this study were three English teachers in senior high school inSingaraja. Data from this study were collected through document study and interviews. The result ofthis study indicates that the materials used by English teachers in senior high schools in Singaraja arein the level authentic.